Potassium changes the relationship between receptor occupancy and the inotropic effect of cardiac glycosides in guinea-pig myocardium. - Bachmaier, A. (1985)
K+ (2.4-15.6 mmol l-1) antagonized the positive inotropic effect of dihydro-ouabain. The concentration-effect curves became steeper with the shift to higher concentrations of the glycoside. At 1.2 mmol l-1 Ca2+, an increase in K+ from 2.4 to 12 mmol l-1 required tenfold higher concentrations of dihydro-ouabain to produce equal inotropic effects. This factor was reduced to four at 3.2 mmol l-1 Ca2+. The same change in K+ concentration, at 1.2 mmol l-1 Ca2+, diminished the inotropic effect of ouabain on rested-state contractions by a factor of six. The positive inotropic effect of Ca2+ was also antagonized by K+ (1.2-12 mmol l-1). Reduction of Na+ from 140 to 70 mmol l-1 abolished the antagonistic action of K+ (1.2-8.0 mmol l-1). Moreover the inotropic effect of Ca2+ was enhanced. Reduction of Na+, from 140 to 70 mmol l-1, antagonized the positive inotropic effect of dihydro-ouabain more at low (2.4 mmol l-1) than at high (8.0 mmol l-1) K+. Accordingly, the extent of the dihydro-ouabain-K+ antagonism was reduced. When the K+ concentration was increased from 2.4 to 12 mmol l-1, [3H]-ouabain binding was reduced by a factor of three. This is less than the reduction in the inotropic effectiveness of ouabain or dihydro-ouabain. Reduction of stimulation frequency from 1 to 0.1215 Hz did not significantly alter the antagonistic effect of K+. Diminution of Vmax of the action potential was observed only at K+ concentrations greater than 5.9 mmol l-1, whereas the resting membrane potential was continuously depolarized over the entire range of K+ concentrations. The results support the view that the reduction in receptor affinity cannot be the sole cause of the antagonism between the glycoside and K+. Impairment of passive Na+ influx during diastole, due to the K+-dependent depolarization of the resting membrane potential, contributed to about one half of the glycoside-K+ antagonism.